PRODUCT QUALITY CONTROL ANALYSIS TO MINIMIZE PIRN BOBIN SUPPLY'S DEFECTS WITH SIX SIGMA METHOD IN THE TEXTILE INDUSTRY (CASE STUDY PT. X-MAJALENGKA) - Salis Fauzi, Leni; Alamsyah P, Agus; Rizanuddin N, Hafni (Jurnal Mekanika dan Manufaktur, 2021)
The industrial sector is now a new foundation for the people of Indonesia. Quality is a key factor that brings business success, growth and increasing competitive position. The quality of a product is defined as the degree or extent to which products or services are able to satisfy the desires of consumers (fitness for use). In fact, if the product or product can not achieve precisely the purpose for which the item is intended or used, it does not necessarily mean that the consumer or the buyer will make a complaint to the producer. Different types of methods are developed and applied by industrial societies to produce products of better quality. Six sigma is a method of controlling and improving the quality of Motorola implemented by the company since 1986 and then used by companies large-scale international level.PT. X-Majalengka, the company is engaged in semi-finished textiles. Research carried out is in part preparation before the weaving process, namely the winding. The number of mismatches that continued to occur on the production floor Grade A winding into a decrease in Gray cloth. Yarn is the main ingredient pembutan fabric gray, yarn used affects the quality of gray cloth produced, of course, to produce gray cloth that grade A then the thread used to be quality yarn, a process for producing quality yarns is the preparation stage is the process of winding, Good thread the warp or weft will experience the process of winding. By using six sigma analysis showed that the quality Pirn supply bobbins produced by the company has a good process capability. Based on Sigma value calculation, the average value of the company is 2.52 sigma with 169.31 Defect per million Opportunitas (DPMO). This shows a consistent pattern of DPMO and sigma achievement, indicating that the production pattern has been properly managed. And types of disabilities in Pirn product supply bobbins grouped into three types. This type of disability is calculated frequency for 1 year of production from July 2016 until June 2017 that is hairy 72 pirn, deflated loops154 and 245 pirn pirn.